(untitled) (Damascus University Journal for the basic sciences, 2022)
The concentration of Ceftriaxone Sodium was determined by using Reversed Phase Liquid Chromatography (RP-HPLC) equipped with UV detector on wavelength of 254 nm and column C18 (25cm, 4.6mm,5µm). The mobile phase consists of (Buffer 93%: 2-Propanol 7%) and the buffer is a solution of 5.1 g/L of Sodium Acetate Trihydrate adjusted to pH=6 with glacial acetic acid. The flow rate adjusted to 1.2 mL/min. Results were linear in the range of (8 – 178) µg/mL with correlation coefficient R2=0.9999. The relative standard deviation of (n=6) replicates was RSD%=0.74, This method was characterized by high precision, high specificity, low cost and suitable for quality control in pharmaceutical industries.